Research on the inheritance value and protection mechanism of Taijiquan from the perspective of intangible Cultural Heritage - Liu, Linli (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: In December 2020, Taijiquan was included in UNESCO’s Representative List of the Intangible Cultural Heritage of Humanity, marking the recognition of China’s excellent traditional culture throughout the world and fully reflecting China’s increasing level of protection and performance of intangible cultural heritage. It is of great significance to inherit and carry forward the fine traditional Chinese culture, highlight the innovation and creativity of the Chinese nation, enhance the international influence of Chinese culture, and promote people-to-people exchanges and mutual learning among civilizations. Under the influence of increasingly frequent global cultural exchanges, Tai Chi has expanded its development space, but at the same time, it has impacted the inheritance of Tai Chi. This paper studies the inheritance value and protection mechanism of Taijiquan from the perspective of intangible cultural heritage protection. Methods: This paper adopts literature, logical analysis and other methods. Results: Taijiquan, as an intangible cultural heritage, should be protected in accordance with the principles of authenticity, integrity and vitality. Manifestations of lack of authenticity protection in the inheritance process of taijiquan : (1) alienation of technology inheritance. With a history of more than 300 years, Tai Chi has formed many schools. However, the remarkable characteristics of different schools are due to the continuous exploration of "the way of defence and attack", especially after Yang Luchan taught boxing to the society, Tai Chi was loved by the high officials and dignitaries, and the functional value of Tai chi was transferred from the secure life to the physical fitness; (2) Loss of cultural heritage. Influenced by Confucianism and Taoism, Taijiquan attaches great importance to "self-cultivation" and "both form and spirit". It emphasizes the "integration of inside and outside" and the "worship of martial arts and morality", which is a kind of body culture of "practicing both inside and outside". (3) Distortion of theoretical inheritance. Ma Ming, dean of Taijiquan College of Henan Polytechnic University, pointed out that the technical movements of Taijiquan contain profound theoretical connotation, which is also the charm of taijiquan. Without theoretical interpretation, the technical movements of Taijiquan appear pale and boring. Therefore, both theory and technology should be paid attention to in the process of inheriting and protecting. The reasons for the lack of taijiquan authenticity protection are as follows: first, the change of times has an important impact on the authenticity of Taijiquan; Second, diversified development leads to changes in the authenticity of Tai Chi. Manifestations of the lack of overall protection of tai chi: (1) the imbalance between the development of theory and technology. He Huichao, the 8th generation descendant of He style Taijiquan, pointed out that both theory and technology are important elements of Taijiquan. However, from the perspective of various existing propagation, it is relatively common to put more emphasis on technology than theory. (2) Lack of cultural environment cultivation of Tai Chi. The integrity principle of cultural heritage protection emphasizes not only the protection of cultural heritage itself, but also the cultivation and protection of the living environment of cultural heritage. The reasons for the lack of overall protection of Taijiquan are as follows: first, with the development of The Times, attack and attack is no longer the demand of the public, but instead fitness and entertainment. As a result, the theory and technology of attack and attack that taijiquan first pursued were ignored in the process of transmission, thus affecting the integrity of taijiquan theory and technology. Second, the essence of Tai Chi has always been held in the hands of a few successors, which has affected the integrity of the spread of Tai Chi. Third, profound theories and profound cultural deposits make it difficult to spread tai Chi as a whole. Fourthly, there are great differences in the theories and techniques of coaches at different levels. They often teach taijiquan theory and techniques according to their personal understanding. Some even practice Taijiquan dance, which also brings bad effects to the integrity of taijiquan. Fifth, many training courses and promotion centers have staged training for students, and students can only learn few theories and techniques, which will also cause the loss of the integrity of Tai Chi in the transmission. Sixth, the chaotic market communication environment has affected the overall communication effect of taijiquan, severely dampened the enthusiasm of high-level boxers to engage in taijiquan training, resulting in the failure of standardized Taijiquan to spread to more people, and then affected the overall effect of taijiquan communication. The adjustment path of Taijiquan inheritance and protection in China from the perspective of intangible cultural heritage protection: establish taijiquan coordinated development mechanism, improve the market access mechanism of taijiquan teachers and the certification and management mechanism of folk boxers, improve the taijiquan inheritance and protection mechanism, establish and improve the policy and system of Taijiquan inheritance and protection. Conclusion: As a representative of Chinese traditional culture, Taijiquan has been incorporated into the national development strategy, which shows that the country attaches great importance to the development of Taijiquan. With the promotion of the "One Belt and One Road" development strategy, Tai Chi, as a cultural representative, is bound to be more open to go abroad and spread around the world, thus ushering in a new peak of communication and development. However, in the context of the rapid spread of Tai Chi, how to do a good job of tai Chi protection has become a difficult problem. Dissemination and protection are important bases for the development of Taijiquan, and they are also a pair of contradictions. Blindly emphasizing dissemination while ignoring protection, the development of Taijiquan is bound to deviates from the scientific track. At present, as the first intangible cultural heritage of China, Tai Chi has shown various problems in the process of transmission, which requires the tai chi community to strengthen the awareness of crisis, take advantage of the good situation, accelerate the transmission and development of Tai chi, and do a good job in the protection of Tai chi.